Heterogeneous impacts of land quality on household income in Vietnam’s north central region - Nguyen, Yen Hai Thi; Tran, Tuyen Quang (Asian Journal of Agriculture and Rural Development, 2025)
This paper examines the heterogeneous effects of land quality on household income in Vietnam’s North Central region. It aims to explore how land quality influences income distribution and whether its benefits are shared equally among households. We employ an instrumental variable quantile regression to analyze the impact of land quality across different income levels while addressing potential endogeneity issues. This approach allows for a more nuanced understanding of how land quality affects households at various points in the income distribution. Our results indicate that only households above the median income level benefit from better land quality, while poorer households experience no significant gains. Land quality positively influences crop income for all groups, but its effects are stronger for those with higher crop incomes. This suggests that wealthier households benefit disproportionately from improved land quality. The findings challenge conventional methods that focus on mean effects, highlighting the importance of accounting for heterogeneity when analyzing land quality’s impact. Ignoring these differences may lead to misleading policy recommendations. The study underscores the need for targeted government policies to support poorer households in utilizing their land more effectively. Policymakers should design interventions that enhance agricultural productivity for lower-income farmers to ensure more equitable benefits from land quality improvements.